CONGENITAL HEART DEFECTS AND NON-CARDIAC MALFORMATIONS IN PATIENTS WITH A NORMAL KARYOTYPE, ODISHA: A COHORT STUDY. - Keshri, Ravi (Student’s Journal of Health Research Africa, 2024)
Background Congenital heart defects (CHDs) are the most common type of birth defect, frequently associated with non-cardiac malformations, even in patients with normal karyotypes. Understanding these associations can enhance diagnosis, management, and outcomes. The study investigated the prevalence and types of non-cardiac malformations in patients with CHDs and normal karyotypes and identified significant associations between these anomalies. Methods A retrospective observational study was conducted. The study included 300 patients with CHDs and normal karyotypes. Data were collected from medical records, including demographic information, types of CHDs, and non-cardiac malformations. Statistical analysis was performed, employing chi-square tests and logistic regression. Results The participants comprised 160 males (53.3%) and 140 females (46.7%), with a mean age of 3.5 years. The study found that 33.3% of patients had musculoskeletal anomalies, 28.3% had genitourinary anomalies, and 21.7% had gastrointestinal anomalies. Significant associations were observed between VSD and musculoskeletal anomalies (χ² = 12.5, p = 0.0004) and ASD and genitourinary anomalies (χ² = 5.8, p = 0.02). A family history of anomalies was a significant predictor of multiple congenital anomalies (OR = 3.2, 95% CI: 1.8-5.7, p =0.00002). Surgical interventions led to favorable outcomes in 83.3% of patients. Conclusion The study highlights a high prevalence of non-cardiac malformations in patients with CHDs and normal karyotypes, with significant associations between specific CHDs and certain non-cardiac anomalies. These findings underscore the necessity for a multidisciplinary approach to improve diagnosis and management, as well as the importance of considering family history in assessing risks for multiple congenital anomalies. Recommendations Future research is needed to explore the genetic and developmental mechanisms underlying these associations. A multidisciplinary approach should be implemented in clinical practice to improve diagnosis and management of patients with CHDs and associated non-cardiac malformations.